The Role of Visual Design in Building Brand Image to Increase Consumer Loyalty in the Digital Era - Zaky Haidar, Alif (Side: Scientific Development Journal, 2024)
In the digital era, brand image is a crucial factor in influencing consumer loyalty. This research explores the role of visual design in building brand image and its impact on increasing consumer loyalty. Using a qualitative approach, especially literature studies through library research, this article examines various theories and previous research that highlight the importance of visual design elements such as logos, color schemes, typography, and aesthetic consistency in creating a strong brand identity. These design elements are able to evoke emotional responses, build trust, and shape positive consumer perceptions, ultimately increasing brand loyalty. In addition, this research also discusses how digital platforms, such as websites and social media, strengthen the role of visual design in today's increasingly competitive market. The study results show that consistent and focused visual design can increase a brand's attractiveness in the eyes of consumers, as well as being an effective means of communication to better convey brand values. Therefore, it is important for companies to understand that visual design not only functions as an aesthetic element, but also as a strategic tool that can encourage consumer loyalty to brands in this digital era.